Laboratory experiments [for] Chemistry and the living organism - Macaulay, David B. (Wiley, 1996)
The latest version of this popular textbook updates the content and format of previous editions to make it more appealing to students and more useful to instructors. Concentrates on the relationship between basic chemical concepts and the chemistry of living organisms. Delves into such topical issues as alcoholism, radiation therapy, and effects of food chemicals on the brain. This edition features a STEP problem solving strategy which provides a consistent method to solve all problems in the book, an extensive glossary plus full-color art work.